EMOTIONAL SALARY AS A MANAGEMENT TOOL: IMPORTANCE ATTRIBUTED BY NURSING PROFESSIONALS - Pires, Vladia Pinheiro de Sousa; Perroca, Marcia Galan (Cogitare Enfermagem, 2023)
Objective: to identify the importance attributed by nursing professionals to the proposed components of emotional salary, and to verify the association with the participants’ sociodemographic and work-related variables. Method: exploratory study with 172 professionals from an oncology hospital in the state of São Paulo - Brazil, carried out in 2021. A questionnaire containing 40 components of emotional salary was constructed and validated. Measures of central tendency and non-parametric tests were used for the analysis. Results: nurses highlighted the opportunity for career progression and feeling respected - 3.8 (0.4); and technicians/auxiliaries, feeling respected by colleagues, collaborative action, and the social importance of work - all with 3.7 (0.5). There was an association between the scale scores and schooling (p ≤0.05). Conclusion: Most of the components of emotional salary are valued, especially those related to professional relationships and working conditions. The findings can guide personnel policies in organizations, favoring job satisfaction, quality of care and organizational results.